OPTIMIZATION OF WORKER WORK ENVIRONMENT, ROBOTS, AND MARKETING STRATEGY: THE IMPACT OF DIGITAL-BASED SPATIOTEMPORAL DYNAMICS ON HUMAN RESOURCE MANAGEMENT (HRM) - Zaenal Aripin; Faisal Matriadi; Sri Ermeila (Organisasi Kreatif Indonesia Emas, 2024)
In the ever-evolving digital era, companies are faced with increasingly complex challenges in managing the work environment for both employees and robots, as well as formulating effective marketing strategies. Digital spatiotemporal dynamics affect various aspects of human resource management (HRM), including recruitment, development, talent retention, and the interaction between humans and machines in the workplace. Therefore, it is crucial to understand the impact of these dynamics on HRM to create an optimal work environment and effective marketing strategies. This research aims to analyze the impact of digital spatiotemporal dynamics on human resource management, particularly in the context of optimizing the work environment for employees and robots, as well as relevant marketing strategies. The main objective is to identify the challenges and opportunities faced by organizations in managing these dynamics, and to formulate best practices in addressing these changes. The research method employed in this study is qualitative descriptive. Data were collected through a literature review of relevant sources, including journals, articles, and related books. Analysis was conducted by summarizing and synthesizing findings from various sources, as well as identifying patterns and trends that emerge in the context of optimizing the work environment for employees, robots, and marketing strategies in digital spatiotemporal dynamics. The results of the study indicate that digital spatiotemporal dynamics have a significant impact on human resource management. Digital transformation has changed the way organizations recruit, develop, and retain talent, as well as interact with customers through adaptive and innovative marketing strategies. Challenges include integrating complex technologies, data protection, and the need for new digital skills, while opportunities include increased operational efficiency, personalized content, and access to global markets.